Effects of a flavoring agent on finishing swine performance - Johnston, M.E.; Stoner, G.R.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A finishing study was conducted to evaluate the effect of a commercially available flavoring agent on finishing pig performance. One hundred ninety-two finishing pigs were used in the study. Half the pigs received the finishing diet with added flavor, whereas the other half received the same diet without flavor. There were no differences in average daily gain (ADG) between pigs fed either the flavored or non-flavored feed. However, the pigs receiving flavored feed had significantly higher average daily feed intake for the entire trial. Feed efficiency was better for pigs fed the non-flavored diet than for those fed the flavored diet. These results indicate that the addition of a flavor to finishing pig diets will enhance feed intake with minimal effects on growth performance.
Keywords: Swine; Finishing pigs; Flavor; Flavoring agent